The Concept and Competitiveness of Agile Organization in the Fourth Industrial Revolution’s Drift - Balog, Katalin (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
The corporate competitiveness is constantly being shaped by the Fourth Industrial Revolution, the explosive development of technology, the globalization and the hyper-competition. The VUCA status has now become a permanent reality: volatility and complexity cannot be traced to traditional corporate operations. The Industry 4.0 projects a physical, a digital and a biological megatrend such as advanced robotics, artificial intelligence, new materials, personalized healing, self-driving cars. The usage of the resources and the knowledge sharing, the global economy is experiencing mutations such as the sharing economy, the peer to peer economy, the gig economy in the labor market and the bigdata in planning. Meanwhile, the disruptive innovations are transforming industries and gaining exponentially competitive advantage. The special business concepts were born and whom cannot be handled by models of classic macro and micro economics: the largest taxi company in the world does not own any taxis (Uber), the largest accommodation company does not own any property (Airbnb), the largest telecommunication company has no infrastructure (Skype), the world's most valuable retailer has no inventory (Alibaba), the most popular media doesn't create its own content (Facebook), the world's largest cinema doesn't have its own movie (Netflix). In the meantime, those are treasuring huge profits, business influence and information capital. The competitiveness of their agile way of working can be proved. These calls for changes not only in the market, but also in organizational and individual terms. An adaptive corporate structure and leadership, a self-organizing group, an agile working method hold the companies in the direction of growing track and changes in the future.